Anonymous Secure Reputation Routing System For Selective Forwarding Attacks In Wireless Sensor Networks - Dr.V.Thirunavukkarasu, Dr.A.Senthil kumar, K.T.JayaBharathi (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Networks (WSNs) are more vulnerable to various security threats. One of the most important threat is selective forwarding attacks which maliciously drop a subset of packets which are being forwarded hence it makes the resource unavailable to its intended users. Due to this drop the packet loss rate is high and hence it poses a great challenge to differentiate between the normal loss and the malicious drop. In this paper, an anonymous secure routing and reputation system which detects the compromised nodes are combined where the malicious drop can be identified and reduced. Simulation results demonstrate that anonymous secure reputation routing system is more efficient than the reputation system. Further this type of authenticated secure routing improves the data delivery ratio of the network.